EFEKTIVITAS VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPA DI MASA PANDEMI COVID 19 PADA SISWA KELAS IV SD INPRES LANRAKI I KOTA MAKASSAR - Annisa Imaniah, Andi Nurul; Hamid, Sundari; St. Muriati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
This research was conducted with the aim of knowing the effectiveness of the instructional videos on the science learning outcomes during the covid-19 of fourth grade students of SD Inpres Lanraki 1 Makassar. This type of research is an experimental study with a Pre-Experimental One Group Pretest-Posttest research design. The population was all students of SD Inpres Lanraki 1 Makassar. The sample of this research was taken using cluster sampling technique, namely 25 of the fourth-grade students. The data collection technique of the study was the test and documentation techniques which were analysed using paired t-test using SPSS. The research data shows that t count > t table is 14.849> 1.710, consequently, H1 is accepted and H0 is rejected. Thus, it can be concluded that the instructional video is effective on students' science learning outcomes.